Penerapan Metode Adams Bashforth Moulton melalui Persamaan Logistik dalam Memprediksi Jumlah Penduduk di Kota Medan - Febya Br Nasution; Dian Cintya Hasmi Br Pohan; Rico Pradana Dita; Rizq Alwi Marpaung (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
One of the biggest problems faced by several countries is the rapid increase in population growth, especially in an archipelagic country like Indonesia. One of the cities in North Sumatra Province that has experienced a significant increase in population is Medan City. This study discusses the population growth each year in Medan City. This study predicts the future population by combining historical data on population, birth rate, death rate, and migration using the Adams-Bashforth-Moulton approach in logistic modeling. This study shows the progress of the approach in predicting the population growth of Medan City. With an area of ​​265.10 thousand km2, and a population reaching 2,474,166 people in 2023. The Adams-Bashforth-Moulton method as a logistic growth model is very effective for decision making in predicting population growth in the city of Medan.